Rituximab and Acute Retinal Necrosis in a Patient with Scleromalacia and Rheumatoid Arthritis. (2nd January 2016) - Schuler, Sarah; Brunner, Matthias; Bernauer, Wolfgang
Abstract: Background : Rituximab is a widely used biologic agent, which has shown favourable results in the treatment of vasculitis. But immunosuppressive treatment also bears the risk of severe complications. Methods : A patient with rheumatoid arthritis, progressive scleromalacia, and acute retinal necrosis on therapy with rituximab is reported. Results : For the first time, a correlation between rituximab and acute retinal necrosis in a patient with progressive rheumatoid scleromalacia is shown. Conclusions : Although rituximab is a promising biologic agent for the treatment of autoimmune diseases, it bears the risk of reactivation of viral infections, including the onset of acute retinal necrosis.